2006
DOI: 10.1007/s10508-006-9085-8
|View full text |Cite
|
Sign up to set email alerts
|

The Playmate and Play Style Preferences Structured Interview: A Comparison of Children with Gender Identity Disorder and Controls

Abstract: The present study compared the sex-typed preferences for playmates and play styles in children referred for concerns about their gender identity development (199 boys, 43 girls) with that of controls (96 boys, 38 girls). Each child was administered the Playmate and Play Style Preferences Structured Interview (PPPSI) developed by Alexander and Hines (Alexander, G. M., & Hines, M. (1994). Child Development, 65, 869-879). In the two single dimension conditions (playmates and play styles), the controls significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
(42 reference statements)
3
23
0
6
Order By: Relevance
“…This finding is consistent with other gender-related measures for which we have also found higher levels of cross-gender behavior in the threshold patients than in the subthreshold patients (e.g., Fridell et al, 2006;Zucker & Bradley, 1995). Although our use of the GIQC measure provided some evidence for the concurrent validity of the clinician-based diagnosis of GID, we recognize that this result should be interpreted with some caution because we did not have data on interclinician reliability of the diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other gender-related measures for which we have also found higher levels of cross-gender behavior in the threshold patients than in the subthreshold patients (e.g., Fridell et al, 2006;Zucker & Bradley, 1995). Although our use of the GIQC measure provided some evidence for the concurrent validity of the clinician-based diagnosis of GID, we recognize that this result should be interpreted with some caution because we did not have data on interclinician reliability of the diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, variations in toy choices may influence development of academic skills (e.g., blocks and spatial abilities vs. dolls and verbal abilities), whereas variations in play partners may influence the development of social skills. Furthermore, peers may be more rejecting of a child for having extreme cross-sex activities than having cross-sex friends (Fridell, Owen-Anderson, Johnson, Bradley & Zucker, 2006). Even though activity engagement and peer selection are related, they are not highly overlapping, suggesting that it would be interesting in future research to conduct an IPP analysis of children’s gender-typed activities.…”
Section: Discussionmentioning
confidence: 99%
“…Children with GID usually prefer playmates and toys of the opposite sex and they also have their play styles. There are a number of studies that have examined whether gender-referred children showed more cross-gender behaviors and feelings than non-referred children (e.g., Fridell, Owen-Anderson, Johnson, Bradley, & Zucker, 2006; Johnson et al, 2004; Cohen-Kettenis, Wallien, Johnson, Owen-Anderson, Bradley, & Zucker, 2006; for an overview, see Zucker & Bradley, 1995). Fridell et al (2006) compared the preferences for playmates and play styles in gender-referred children (199 boys, 43 girls) with those of controls (96 boys, 38 girls): The gender-referred children significantly preferred other-sex playmates and cross-sex play styles.…”
Section: Introductionmentioning
confidence: 99%